Legal Children in Pregnant Marriage: A Juridical Analysis of Indonesian Positive Law - Abidin, M. Nur; Basit, Abdul (Alhurriyah, 2022)
The discourse of pregnant marriage is always interesting to study from a legal perspective, both Islamic and civil law, the different views of the fuqoha and also the controversy in understanding whether or not pregnant marriage is permissible. Different understandings are found in KHI which on one side is a normative backing and on the other side opens the room for adultery. As a result of being pregnant before, it was not a problem because children born during marriage became legal children, regardless of the age of the child's womb when both parents performed the marriage contract, while SE Director General of Islamic Guidance and Hajj Affairs No: D/ED/PW.01/03/1992 Regarding the Instructions for Completing Marriage, Divorce, Divorce and Referral Forms (NTCR), it is stated that a legitimate child is a child born at least more than six months from marriage, if the child born less than six months is interpreted as the child of the mother.One of the requirements for marriage administration is a birth certificate, if the first child is a girl, must be accompanied by a quote from the marriage book of both parents at the time of registration, this is to check the marriage date of both parents and also be equipped with a birth certificate to check when the child was born. So far, even if the birth certificate contains the names of both parents, but when confronted at the time of the examination the child was born less than six months after the marriage contract, the father's name was not listed in the marriage certificate. In line with this, from a legal perspective, the binding force between KHI and the Circular Letter is stronger than the KHI or Circular in the Registration and Implementation of Marriages.